A label-free and turn-on fluorescence sensor for sensitive and selective detection of iodide using carbon nanodots/silver nanocomposites1. Issue 10 (21st May 2015) - Gao, Buhong; Tang, Ying; Sun, Haijun; Xuan, Yan; Xu, Li; Huang, Chaobo
<x xml:space="preserve">Abstract</x> Based on the principle of fluorescence recovery, we propose a simple label-free and turn-on method for the detection of I− ions with high selectivity and sensitivity by using fluorescent Cdots/Ag nanocomposites in aqueous media.